Monitoring the colonization and infection of legume nodules by Micromonospora in co-inoculation experiments with rhizobia - Benito, Patricia (Sci Rep, 2017)
The discovery that the actinobacterium Micromonospora inhabits nitrogen-fixing nodules raised questions as to its potential ecological role. The capacity of two Micromonospora strains to infect legumes other than their original host, Lupinus angustifolius, was investigated using Medicago and Trifolium as test plants. Compatible rhizobial strains were used for coinoculation of the plants because Micromonospora itself does not induce nodulation. Over 50% of nodules from each legume housed Micromonospora, and using 16S rRNA gene sequence identification, we verified that the reisolated strains corresponded to the microorganisms inoculated. Entry of the bacteria and colonization of the plant hosts were monitored using a GFP-tagged Lupac 08 mutant together with rhizobia, and by using immunogold labeling. Strain Lupac 08 was localized in plant tissues, confirming its capacity to enter and colonize all hosts. Based on studying three different plants, our results support a non-specific relationship between Micromonospora and legumes. Micromonospora Lupac 08, originally isolated from Lupinus re-enters root tissue, but only when coinoculated with the corresponding rhizobia. The ability of Micromonospora to infect and colonize different legume species and function as a potential plant-growth promoting bacterium is relevant because this microbe enhances the symbiosis without interfering with the host and its nodulating and nitrogen-fixing microbes.